2020
DOI: 10.1093/cercor/bhaa266
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis of Neonatal White Matter Microstructure

Abstract: A better understanding of genetic influences on early white matter development could significantly advance our understanding of neurological and psychiatric conditions characterized by altered integrity of axonal pathways. We conducted a genome-wide association study (GWAS) of diffusion tensor imaging (DTI) phenotypes in 471 neonates. We used a hierarchical functional principal regression model (HFPRM) to perform joint analysis of 44 fiber bundles. HFPRM revealed a latent measure of white matter microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 121 publications
1
6
0
Order By: Relevance
“…For the detected protein-coding genes, we perform lookups in the NHGRI-EBI GWAS catalog ( Buniello et al 2019 ) and previous GWASs for white matter to explore their previously reported gene-trait associations. Our results replicate 415 genes reported by Zhao et al (2021a) and some other genes reported in previous studies for human white matter ( Sprooten et al 2013 , 2014 ; Verhaaren et al 2015 ; Jian et al 2018 ; Rutten-Jacobs et al 2018 ; Zhao et al 2021b ; Zhang et al 2021 ) and find 204 novel genes ( Supplemental Table S7 ). Of the 619 detected genes, 227 have previously been implicated in cognitive function, education, neuroticism, neuropsychiatric disorders, neurodegenerative diseases, and reaction time, such as ARIH2 ( Lee et al 2018 ; Kulminski et al 2022 ) and PTCH1 ( Nagel et al 2018 ; Thorp et al 2021 ; Okbay et al 2022 ).…”
Section: Resultssupporting
confidence: 89%
“…For the detected protein-coding genes, we perform lookups in the NHGRI-EBI GWAS catalog ( Buniello et al 2019 ) and previous GWASs for white matter to explore their previously reported gene-trait associations. Our results replicate 415 genes reported by Zhao et al (2021a) and some other genes reported in previous studies for human white matter ( Sprooten et al 2013 , 2014 ; Verhaaren et al 2015 ; Jian et al 2018 ; Rutten-Jacobs et al 2018 ; Zhao et al 2021b ; Zhang et al 2021 ) and find 204 novel genes ( Supplemental Table S7 ). Of the 619 detected genes, 227 have previously been implicated in cognitive function, education, neuroticism, neuropsychiatric disorders, neurodegenerative diseases, and reaction time, such as ARIH2 ( Lee et al 2018 ; Kulminski et al 2022 ) and PTCH1 ( Nagel et al 2018 ; Thorp et al 2021 ; Okbay et al 2022 ).…”
Section: Resultssupporting
confidence: 89%
“…GWAS Catalog look-ups for the effects of genetic variants in APCS identified a previously reported association with white-matter microstructure 34 (Fig. S3; Table S9).…”
Section: Genome-wide Meta-analysis Of Plasma Sap Valuesmentioning
confidence: 88%
“…In adults, estimates for FA range from 72% to 88% ( 25 ). Despite large variations in heritability estimates across individual tracts, a single latent measure of white matter microstructure accounts for a great deal of heritable variation in neonates (50%) ( 26 ). Similarly, individual differences in regional CT and SA appear to be driven by a common set of genetic factors influencing cortical structure at the global level ( 19 ).…”
Section: Heritabilitymentioning
confidence: 99%
“…The investigators also compared their results to large-scale neuroimaging GWASs in adolescents and adults and concluded that genetic determinants of global brain volumes are highly distinct at different ages. In a subsequent GWAS of white matter microstructure in neonates, an intronic SNP in PSMF1 was significantly associated with a tractography-based factor capturing shared variation in FA across 44 white matter bundles ( 26 ). Additional loci nearing genome-wide significance were in or near genes with roles in axon growth and guidance, fasciculation, and myelination including B3GAT1 , TENM2 , NFATC1 , and MAP3K13 .…”
Section: Heritabilitymentioning
confidence: 99%
See 1 more Smart Citation